Tafsir Putusan Mahkamah Konstitusi Nomor 55/PUU-XVIII/2020 Terhadap Syarat Kepesertaan Partai Politik dalam Pemilu 2024 - Adelline Syahda (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The registration of political parties participating in the election should pay attention to the perspective of justice both in terms of regulation and practice. In order to participate in the election, a political party must have passed verification by the KPU. The terms of participation of political parties to participate in elections are regulated in Article 173 of Law Number 7 of 2017 concerning Elections. Efforts to obtain fair and equal treatment before the law in the registration of election participants can be seen through several judicial reviews of the Constitutional Court Decisions. This balance of treatment is based on equality of opportunity in the participation of the nation's life as a contribution in the political field according to Article 28D of the 1945 Constitution. Lastly, Decision Number 55/PUU-XVIII/2020 divides the qualifications of political parties as candidates for the 2024 general election into two, namely first, political parties that are only verified administratively, secondly, political parties that are verified administratively and factually. This study aims to describe the requirements for political parties to participate in elections according to the Election Law and the implications of the issuance of the Constitutional Court Decision on the development of the meaning of verification. The writing uses normative research methods. This research will provide findings on the two formulations of the problem and recommendations as conclusions.Keywords: Political Parties; Party Verification; Elections AbstrakPendaftaran partai politik peserta pemilu sudah seharusnya memperhatikan perspektif keadilan baik secara regulasi maupun praktik. Untuk menjadi peserta pemilu, partai politik harus telah ditetapkan lulus verifikasi oleh KPU. Syarat kepesertaan partai politik menjadi peserta pemilu diatur dalam Pasal 173 UU Nomor 7 Tahun 2017 tentang Pemilu. Upaya untuk mendapatkan perlakuan yang adil dan sama dihadapan hukum dalam pendaftaran peserta pemilu dapat dilihat melalui beberapa judisial review Putusan Mahkamah Konstitusi. Keseimbangan perlakuan ini didasari atas kesamaan kesempatan dalam peran serta kehidupan berbangsa bernegara sebagai kontribusi di bidang politik sesuai Pasal 28D UUD 1945. Terakhir Putusan Nomor 55/PUU-XVIII/2020 membagi kualifikasi partai politik calon peserta pemilu 2024 atas dua yaitu pertama, politik yang hanya diverifikasi secara administrasi, kedua, partai politik yang dilakukan verifikasi secara administrasi dan factual. Kajian ini bertujuan mendeskripsikan syarat partai politik menjadi peserta pemilu menurut UU Pemilu serta implikasi terbitnya Putusan Mahkamah Konstitusi terhadap perkembangan pemaknaan verifikasi. Penulisan menggunakan metode penelitian normatif. Penelitian ini nantinya akan memberikan temuan atas kedua rumusan masalah tersebut dan rekomendasi sebagai simpulan.Kata Kunci: Partai Politik; Verifikasi Partai; Pemilu